Change Management Strategies in Saudi Government Institutions: An Analytical Study of National Transformation Efforts to Achieve Vision 2030 (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study highlights how change management strategies contribute to achieving the goals of Vision 2030 in the Kingdom of Saudi Arabia. The study aims to analyze the different strategies used in government institutions and determine their effectiveness in promoting national transformation. The study relied on a sample of 166 participants representing several Saudi government institutions, reflecting the diversity of functions and administrative levels to achieve comprehensive and accurate results. The study used a mixed methodology that combined qualitative and quantitative research; data was collected through questionnaires and in-depth interviews with experts in government administration to analyze the processes, challenges and opportunities associated with change management. The results showed that there is a high compatibility between change management strategies and achieving the goals of national transformation, as it emphasized the importance of transformational leadership in promoting an organizational culture that supports innovation and acceptance of change. The results also indicated the role of supportive government policies and procedures in facilitating transformation processes and achieving sustainability. The study showed that cooperation between the public and private sectors is a critical factor in the success of change strategies, as private sector expertise can be leveraged to accelerate the transformation process. Finally, the study provided recommendations to enhance the effectiveness of change management strategies by focusing on employee training and skills development and improving communication between different administrative levels to ensure a shared understanding of change goals and each individual's role in achieving them.
Keywords: Change Management; National Transformation; Vision 2030; Government Institutions; Change Strategies; Institutional Analysis; Sustainable Development